The Nexus Between Public Spending on Education and Economic Growth of Kosovo (Econometric Approach) - Ziberi, Besime; Gashi, Rrezarta; Hodaj, Mimoza (Economics and Business, 2020)
The main aim of this study is to analyse the trend of public spending dedicated to education in case of Kosovo over the years and to measure the impact of public spending in education on economic growth of Kosovo. In order to achieve the aim, the Pearson Correlation has been used and a multifactorial regression model (OLS) has been modified and adapted, where we have determined the Gross Domestic Product (GDP) as a dependent variable and as an independent variable in the model: (i) Public expenditure on secondary education and (ii) Public expenditure on higher education (university). The data used are secondary data from the Kosovo’s State Budget, Ministry of Finance and Transfers, and Kosovo Agency of Statistics. We have come to a conclusion that public spending dedicated to higher education (university) has a positive impact on Kosovo’s economic growth meanwhile public spending on secondary education does not show any effect. The paper suggests further recommendations on public spending policies dedicated to education in order to influence Kosovo’s economic growth.